2012
DOI: 10.1371/journal.pone.0048189
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Control of the Multi-Drug Transporter ABCB1 by Transcription Factor Sp3 in Different Human Tissues

Abstract: The ATP-binding cassette (ABC) transporter ABCB1, encoded by the multidrug resistance gene MDR1, is expressed on brain microvascular endothelium and several types of epithelium, but not on endothelia outside the CNS. It is an essential component of the blood-brain barrier. The aim of this study was to identify cell-specific controls on the transcription of MDR1 in human brain endothelium. Reporter assays identified a region of 500 bp around the transcription start site that was optimally active in brain endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…We found that ERRα can bind with SP3 to regulate the transcription of ABCB1 in OS resistant cells. It has been reported that SP3 may recruit TFIID to the ABCB1 promoter by binding to the second activation domain of Sp3 . In our study, XCT‐790 suppressed transcription of ABCB1 was abolished in cells transfected with si‐SP3.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…We found that ERRα can bind with SP3 to regulate the transcription of ABCB1 in OS resistant cells. It has been reported that SP3 may recruit TFIID to the ABCB1 promoter by binding to the second activation domain of Sp3 . In our study, XCT‐790 suppressed transcription of ABCB1 was abolished in cells transfected with si‐SP3.…”
Section: Discussionsupporting
confidence: 55%
“…It has been suggested that SP3 can regulate the transcription of ABCB1 in various human tissues . We then investigated SP3 was involved in ERRα regulated transcription of ABCB1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SP1 has been implicated in drug resistance, as it positively regulates the expression of ATP-binding cassette transporter (ABCB1), encoded by the multidrug resistance gene MDR1 in Caco2 cells 90 . Cancer stem cells mediate tumor growth, resistance to chemotherapy, and metastasis; high levels of SP1 expression by these colorectal cancer stem cells might contribute to colorectal tumor drug resistance 84 .…”
Section: Roles In the Digestive System And Diseasesmentioning
confidence: 99%
“…Chemotherapy drugs, including adriamycin (ADR), methotrexate and cyclophosphamide, are also applied in patients with osteosarcoma to further kill osteosarcoma cells following amputation surgery (1)(2)(3). However, upon long-term exposure of the tumor cells to chemother apy drugs, the surface of the tumor cells may overexpress P-glycoprotein (P-gp), an adenosine triphosphate-dependent drug efflux pump encoded by the multidrug resistance protein 1 (MDR1) gene (5,6). Overexpressed P-gp can mediate the efflux of a large number of intracellular chemotherapy drugs, thus leading to a significant reduction in the intracellular drug concentration (7,8), which causes drug resistance of tumor cells.…”
Section: Introductionmentioning
confidence: 99%